Advanced T-cell Lymphoma with Penile Involvement Revealed by 18F-FDG PET/CT: A Rare Presentation - Benameur, Yassir; Hammani, Adnane; Bakkali, Jaafar El; Doudouh, Abderrahim (World Journal of Nuclear Medicine, 2025)
T-cell lymphomas are rare malignancies that frequently involve extranodal sites, but penile localization remains exceedingly uncommon. We report the case of a 21-year-old man diagnosed with cutaneous T-cell lymphoma who underwent 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) for initial staging. The scan revealed widespread nodal and extranodal disease, including unexpected intense fluorodeoxyglucose uptake in the corpora cavernosa, in the absence of penile symptoms. Penile involvement in lymphoma, whether primary or secondary, Hodgkin or non-Hodgkin, is exceptionally rare, with very few cases reported—most involving B cell histologies. This finding underscores the utility of PET/CT in identifying clinically silent and atypical disease sites in aggressive lymphomas such as peripheral T-cell lymphoma. The extent of dissemination, including renal, adrenal, bone marrow, and penile involvement, reflects a high tumor burden and portends a poor prognosis. Early recognition of such patterns through PET/CT is essential for appropriate therapeutic planning and may impact patient outcomes.
Keywords: 18F-FDG; aggressive lymphomas; penile involvement; T-cell lymphomas